2010
DOI: 10.1113/jphysiol.2010.196220
|View full text |Cite
|
Sign up to set email alerts
|

Free radical signalling underlies inhibition of CaV3.2 T‐type calcium channels by nitrous oxide in the pain pathway

Abstract: Nitrous oxide (N2O, laughing gas) has been used as an anaesthetic and analgesic for almost two centuries, but its cellular targets remain unclear. Here, we present a molecular mechanism of nitrous oxide's selective inhibition of CaV3.2 low-voltage-activated (T-type) calcium channels in pain pathways. Using site-directed mutagenesis and metal chelators such as diethylenetriamine pentaacetic acid and deferoxamine, we reveal that a unique histidine at position 191 of CaV3.2 participates in a critical metal bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Indeed, Kv7 channels are highly sensitive to oxidation by ROS due to the specific cysteine pocket in the intracellular S2-S3 linker of the channel [27,28]. Interestingly, T-type Ca 2+ channels are also sensitive to redox modulation, albeit in contrast to Kv7 channels, oxidizing compounds and ROS do not activate but inhibit T-type channel activity [21,29,30]. Since ROS generation by NK1 receptor triggering was sensitive to PTX [26] we hypothesized that unconventional signaling cascade causing inhibition of LVA current in DRG neurons by baclofen may also be mediated by a ROSdependent mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Kv7 channels are highly sensitive to oxidation by ROS due to the specific cysteine pocket in the intracellular S2-S3 linker of the channel [27,28]. Interestingly, T-type Ca 2+ channels are also sensitive to redox modulation, albeit in contrast to Kv7 channels, oxidizing compounds and ROS do not activate but inhibit T-type channel activity [21,29,30]. Since ROS generation by NK1 receptor triggering was sensitive to PTX [26] we hypothesized that unconventional signaling cascade causing inhibition of LVA current in DRG neurons by baclofen may also be mediated by a ROSdependent mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Acting as intracellular second messengers, such ROS augmented the activity of inhibitory Kv7 channels providing a mechanism for substance P mediated peripheral endogenous analgesia [26]. Because i) T-type channels are inhibited by oxidizing agents and ROS [21,29,30];…”
Section: Discussionmentioning
confidence: 99%
“…For example, N 2 O, which is one of the anesthetics used in our regimen can generate free oxygen (most likely hydroxy) radicals in the presence of trace metals such as iron and copper (Orestes et al, 2011), both commonly found in biological fluids and neurons. Upregulation of ROS promotes metal-catalyzed protein oxidation, which in turn permanently alters the function of various cellular proteins (Stadtman and Berlett, 1991; Stadtman, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of ROS promotes metal-catalyzed protein oxidation, which in turn permanently alters the function of various cellular proteins (Stadtman and Berlett, 1991; Stadtman, 1993). For example, N 2 O causes inhibition of low-voltage-activated calcium channels by oxidizing critical amino acids in the functional pore of the channel (Orestes et al, 2011). However, having considered that possibility we believe that it is unlikely that N 2 O production of ROS and potential protein oxidation is the main culprit for developmental neurotoxicity we present in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral tests for inflammatory pain after formalin injection were done with mice in a clear Plexiglas chamber prefilled with air at a flow of 6 l/min, as we reported recently (Orestes et al, 2011). Each mouse was first placed in the prefilled chamber to accommodate for 30 min and then removed from the chamber, injected in the plantar side of the right paw with 20 l of 5% formalin or vehicle (15% cyclodextrin), and returned to the test chamber.…”
Section: Behavioral Studiesmentioning
confidence: 99%